Prediction of optimal inclusion levels of neem leaf meal that supports spermatogenesis in rabbits using quadratic optimisation model - Ogbuewu, I. P.; Mbajiorgu, C. A. (International Journal of Agricultural Technology, 2022)
This study was designed to assess the effect of neem (Azadirachta indica A. Juss) leaf meal (NLM) on reaction time and semen quality characteristics of male rabbits. A total of 36 New Zealand white × Chinchilla male rabbits aged 7-8 months were randomly assigned to four dietary treatments designated 0, 5, 10 and 15% NLM with three replications, each having three rabbits for 16 weeks. Semen volume, sperm motility, sperm concentration, total sperm production, abnormal sperm percent and reaction time were assessed at week 4, and thereafter at weeks 6, 8, 10, 12, 14 and 16. Duncan’s test for multiple comparisons was used to test the significant difference between treatment means (p < 0.05). A quadratic equation was used to determine dietary NLM inclusion levels for optimum parameters which were significantly different. Results indicate that addition of NLM at 0.71% supported optimum sperm concentration (12.58 + 1.80 NLM - 1.27 NLM2; p = 0.02). This was higher than the levels of 0.24% and 0.69% needed to improve sperm motility (77.78 – 0.99 NLM – 2.07 NLM2; p = 0.01) and total sperm concentration (14.60 + 0.94 NLM – 0.68 NLM2; p = 0.01), respectively in male rabbits. However, a value of 0.85% NLM gave the least abnormal sperm percent (11.43 – 2.06 NLM + 1.22 NLM2; p = 0.01). It is suggested that dietary NLM inclusion levels of 0.24 – 0.85% supported spermatogenesis in male rabbits. Thus, optimizing the NLM inclusion level in the diet of male rabbits could help to enhance their reproductive efficiency.